Clinical management of infections caused by multidrug-resistant Enterobacteriaceae. (April 2013) - Delgado-Valverde, Mercedes; Sojo-Dorado, Jesús; Pascual, Álvaro; Rodríguez-Baño, Jesús
Enterobacteriaceae showing resistance to cephalosporins due to extended-spectrum β-lactamases (ESBLs) or plasmid-mediated AmpC enzymes, and those producing carbapenemases have spread worldwide during the last decades. Many of these isolates are also resistant to other first-line agents such as fluoroquinolones or aminoglycosides, leaving few available options for therapy. Thus, older drugs such as colistin and fosfomycin are being increasingly used. Infections caused by these bacteria are associated with increased morbidity and mortality compared with those caused by their susceptible counterparts. Most of the evidence supporting the present recommendations is from in vitro data, animal studies, and observational studies. While carbapenems are considered the drugs of choice for ESBL and AmpC producers, recent data suggest that certain alternatives may be suitable for some types of infections. Combined therapy seems superior to monotherapy in the treatment of invasive infections caused by carbapenemase-producing Enterobacteriaceae . Optimization of dosage according to pharmacokinetics/pharmacodynamics data is important for the treatment of infections caused by isolates with borderline minimum inhibitory concentration due to low-level resistance mechanisms. The increasing frequency and the rapid spread of multidrug resistance among the Enterobacteriaceae is a true and complex public health problem.